Implementasi Model Pembelajaran Basic Learning (PjBL) untuk Meningkatkan Pemahaman Siswa dalam Materi Asmaulhusna (Al-Mumit dan Al-Qowiyyu) Kelas V di SD Negeri 37/1 Bajubang - Sulastri, Sulastri; Sumiyati, Sumiyati; Qomaria, Nyimas Siti (TSAQOFAH, 2025)
This study aims to implement the Project-Based Learning (PJBL) model to improve students' understanding of Asmaulhusna, particularly Al-Mumit and Al-Qowiyyu, in the fifth grade of SD Negeri 37/1 Bajubang during the 2023/2024 academic year. The PJBL approach was chosen to help students gain a deeper understanding of the concept of Asmaulhusna while internalizing its values in their daily lives. The research employed Classroom Action Research (CAR) methodology conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. Qualitative data were collected through observations and documentation of student activities, while quantitative data were gathered through summative test results. In the pre-cycle stage, the students' average score was 65, with only 50% achieving the Minimum Mastery Criterion (KKM) of 75. After implementing PJBL in Cycle I, the average score increased to 78, and the percentage of students meeting the KKM rose to 74.07%. In Cycle II, the average score improved further to 90, with all students (100%) meeting the KKM. The findings demonstrate that the PJBL model effectively enhances students’ learning outcomes. Beyond the improvement in scores, students also exhibited active engagement in group discussions, confidence in presentations, and creativity in completing projects such as creating posters and educational videos. The use of video media and Student Worksheets (LKPD) made the material more engaging and relevant for the students. Reflections from each cycle highlighted significant improvements in teaching implementation, particularly in group collaboration and the application of Asmaulhusna values in students’ behavior. With optimal learning outcomes achieved in Cycle II, the study was concluded after two cycles. In conclusion, the PJBL model effectively improves students’ understanding of Asmaulhusna and provides meaningful learning experiences. The study recommends the adoption of PJBL as an innovative method for Islamic Education learning, particularly at the primary school level.